The Irreverent Form - Mills, Rohan Hartley (Auckland University of Technology, 2013)
This is a practiced based research project that inquires into the language of contemporary abstract painting. My painting practice focuses on questions around the renewal and repetition of historical forms. Examining the re-calibration of everyday imagery into a studio context while delimiting previous concerns regarding painting technique, work ethic and the provisional. The objective in this investigation is to gain further understanding of my own studio methodology. I outline the processes and strategies that successfully generate painted forms with a relationship to current dialogues in abstract painting.
Keywords: Painting; Contemporary At; Art